2020
DOI: 10.1177/1420326x20927437
|View full text |Cite
|
Sign up to set email alerts
|

Effects of visual exposure to wood on human affective states, physiological arousal and cognitive performance: A systematic review of randomized trials

Abstract: Background Bringing features of nature indoors can positively influence indicators of human stress. Since wood is a natural material, it may produce similar benefits. The objective of the review was to (1) examine the influence of visual (real or virtual) contact with either real or imitated indoor wooden surfaces on certain stress indicators, that is affective, physiological or cognitive performance outcomes (compared to non-wooden surfaces) and to (2) assess the methodological quality of the reviewed studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 89 publications
1
14
0
Order By: Relevance
“…As for the nature analogues pattern, one key finding relates to the impact of using natural materials such as stone and wood in reducing stress in workplace environments. This observed benefit in work contexts aligns with a systematic review conducted by Lipovac and Burnard et al [42] who emphasized the potential of wood in building construction, although they advised that caution is required before concluding that it affects physiological stress indicators, both due to methodological issues and the rigour of the studies. In any case, this line of research is of special interest as it additional elements that are not necessarily green in workplace environments, thus offering more flexibility in designing these spaces.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As for the nature analogues pattern, one key finding relates to the impact of using natural materials such as stone and wood in reducing stress in workplace environments. This observed benefit in work contexts aligns with a systematic review conducted by Lipovac and Burnard et al [42] who emphasized the potential of wood in building construction, although they advised that caution is required before concluding that it affects physiological stress indicators, both due to methodological issues and the rigour of the studies. In any case, this line of research is of special interest as it additional elements that are not necessarily green in workplace environments, thus offering more flexibility in designing these spaces.…”
Section: Discussionsupporting
confidence: 81%
“…Their findings underscore the significance of individual control and the inclusion of real or artificial plant elements in the design of healthy workspaces, although they do not delve extensively into these aspects. Likewise, another study focused on the use of natural elements indoors, particularly the use of wood, which emphasizes this material's ability to positively influence stress indicators and highlights the need for further research in this field [42]. This combination of research studies highlights the need to further explore how the inclusion of natural elements and the application of biophilic principles can enhance the well-being and mental health of workers in contemporary workplace environments.…”
Section: Benefits Of Biophilic Designmentioning
confidence: 99%
“…Wood is a widely used natural material that is often used in building structures, furniture, and decorative items due to its easy acceptance for consumers and easy processing properties ( Noora et al, 2020 ). It has been found that wood has significant positive effects on people’s health, such as improving concentration and comfort and enhancing sense of security ( Sakuragawa et al, 2008 ; Grote et al, 2009 ; Fell, 2010 ; Alapieti et al, 2020 ; Lipovac and Burnard, 2021 ). Furniture is an essential and practical appliance in office spaces, and people has a positive attitude toward wooden office furniture ( Ridoutt et al, 2002 ; Paluš et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previously we have discussed the benefits of temporal, multi-sensory materials through the lens of architectural discourse, but now we will address the psychophysiological research regarding the benefits of natural materials. The pandemic and climate crisis has caused an increase of poor mental health, but there is also evidence that this is caused by humanity's nature deficit and our switch to spending 80% of our time indoors (Selhub & Logan, 2012;Coulson, 2012;Mcsweeney et al, 2015, p. 127;Lipovac & Burnard, 2021, p. 1021. Research shows that indoor nature exposure (INE) with objects such as wood furnishings and potted plants could improve stress (X.…”
Section: Natural Irregularitymentioning
confidence: 99%
“…Previously, we have discussed how touch is more influential than visual stimuli in switching negativeaffective states to positive ones. A benefit of visual stimuli, however, is that it provides a more passive solution which is more accessible to people, as it does not require the level of engagement that touch does (King & Janiszewski, 2011;Lipovac & Burnard, 2021, p. 1022. This suggests that mycelium bio-composites could provide psycho-physiological benefits across a range of engagement.…”
Section: Natural Irregularitymentioning
confidence: 99%